PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA, MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (BPBD KABUPATEN EMPAT LAWANG) - Erdi Satria Novrata; Ade Tiara Yulinda (UM. Bengkulu, 2023)
The purpose of this study was to determine the effect of leadership style on employee performance, work discipline on employee performance, work motivation on employee performance, and the influence of leadership style, work motivation, work discipline simultaneously on the performance of BPBD employees at Empat Lawang Regency. This research method is associative and data collection by observation, interviews and questionnaires. The population in this study were 38 employees, the data analysis method was